Advances in high voltage engineering - Haddad, A.; Warne, D. F. (London, United Kingdom Institution of Engineering and Technology, 2004)
This book focuses on developments in experimental methods, theory, modeling of HV technology in the past decade. The coverage includes advances in basic understanding and capability in earthing, numerical analysis, optical methods, the physics of air breakdown and partial discharge. It also addresses technological developments in key areas such as SF6 insulation systems, polymeric insulators and power cables, ZnO surge arresters, and pulsed power, The unique blend of reputable contributors and comprehensive subject coverage makes this book and ideal reference source for engineers and researchers.
Electronic reproduction.
Keywords: Electrical engineering; High voltages; Electronic books